Assessing the accuracy of patient report of the 5As (ask, assess, advise, assist, and arrange) for smoking cessation counseling. Issue 3 (1st October 2017) - Flocke, Susan A.; Antognoli, Elizabeth
Abstract : Objective: The 5As framework ( ask, advise, assess, assist, arrange ) is a recommended strategy for smoking cessation counseling in primary care. This study compares patient report with direct observation to assess the degree of recall bias for each of the 5As. Methods: Primary care visits by 107 adult smokers and 16 physicians were audio-recorded. Within 48 hours after the visit, patients completed a survey assessing whether or not smoking was discussed and items specific to each of the 5As. The audio recordings were evaluated to assess the presence of each A . The sensitivity, specificity, positive predictive value, and negative predictive value of patient report versus direct observation were computed. Results: The frequency of the 5As based on evaluation of the audio recording ranged from 13% ( arrange ) to 98% ( ask ). The sensitivity and specificity of patient report were 92% and not applicable for ask, 90% and 50% for assess, 94% and 33% for advise, 90% and 50% for assist, and 85% and 67% for arrange follow-up. Positive predictive values ranged from 28% to 98%; negative predictive values ranged from 0% to 97%. Conclusion: Compared with the gold standard of direct observation, patient report of each of the 5As is reasonably sensitive but not specific. Patients overreport the occurrence of each of the 5As.